2018
DOI: 10.1016/j.ecolind.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of a Sustainable Urban Surface Rating System (SURSIST)

Abstract: Urban surfaces reflect the economic, environmental and social idiosyncrasy of cities, playing a crucial role in the sustainable development of modern civilizations. Thus, the planning and efficient management of the skin of urban areas provides an opportunity to facilitate the fulfilment of the needs of present and future generations. However, there is a lack of specific tools to evaluate the contribution of these surfaces to achieving the Sustainable Development Goals (SDGs), which is the current framework ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…The flexible framework of these methods makes them receptive to covering more sustainability aspects [29], connecting the neighborhood and community, and thus contextualizing them on a broader scale [30]. One of the virtues of rating systems is their ability to evaluate a wide variety of different indicators as a whole, even though these might have different units of measurement [31]. This makes them a unique method by which to obtain indicators that have been proven in the construction sector in different regions around the world, and which in turn, have the support of experts who have participated in the development of each of the systems.…”
Section: Background and Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexible framework of these methods makes them receptive to covering more sustainability aspects [29], connecting the neighborhood and community, and thus contextualizing them on a broader scale [30]. One of the virtues of rating systems is their ability to evaluate a wide variety of different indicators as a whole, even though these might have different units of measurement [31]. This makes them a unique method by which to obtain indicators that have been proven in the construction sector in different regions around the world, and which in turn, have the support of experts who have participated in the development of each of the systems.…”
Section: Background and Research Objectivesmentioning
confidence: 99%
“…In contrast to other studies that focus on the level of the indicators [33][34][35][36][37], this work has centered on the initial situation of RUEs during the SHRS criteria scoring process. The significance of focusing on the study and acquisition of indicators has been shown in several publications, in which it is argued that the success of any evaluation process depends mostly on the indicators used [31,[38][39][40][41].…”
Section: Background and Research Objectivesmentioning
confidence: 99%
“…6c. According to these inferences, urban planning and management strategies concerning air quality should consider taking measures to replace part of the built-up skin of urban areas by lighter surfaces, preferably based on green infrastructure, in order to control atmospheric pollution and contribute to improving sustainability (Jato-Espino et al, 2017).…”
Section: Termmentioning
confidence: 99%
“…As per the sustainable development goal (SDG) 7 of SDG 2015-2030, it is expected to ensure access to affordable, reliable, sustainable and modern energy for all. This SDG 7 aims to accelerate the transition for an affordable, reliable, sustainable energy system to maintain and protect ecosystems (Jato-Espino et al , 2018; Qiao et al , 2019). This study based on sustainability attempts to identify the determinant factors for implementation, characterization, energy demand and proposed technical solution for the energy supply system (Iqbal and Iqbal, 2019; Nayan et al , 2013; Sawle et al , 2016).…”
Section: Introductionmentioning
confidence: 99%